STARCH OF SAGO (Metroxylon sagu rottb) WITH GREEN HOUSE EFFECT DRYER COMBINED BASED ON THICKNESS STACK AND STIRRING - Ma'rub, Ma'rub (Fakultas Pertanian Universitas Tanjungpura, 2019)
The aim of this research was to find the drying rate of sago starch using greenhouse-effect dryer based on layer thickness and stirring frequency. This research used explorative experimental design consist of no-material treatment, 1 cm thickness with stirring frequency of 0, 2, and 4 times/hour, and 2 cm thickness and stirring frequency of 2 and 4 times/hour. Observed parameters were sun radiation, dryer temperature, air humidity, drying rate, and material moisture content. The acquired data were analyzed descriptively. Sago starch drying showed drying rates as follows, thickness of 1 cm without stirring had drying rate of 1.39 kg/hour, thickness of 1 cm with stirring frequency of 2 times/hour had drying rate of 1.22 kg/hour, thickness of 1 cm with stirring frequency of 4 times/hour had drying rate of 1.67 kg/hour, thickness of 2 cm with stirring frequency of 2 times/hour had drying rate of 1.85 kg/hour, and thickness of 2 cm with stirring frequency of 4 times/hour had dring rate of 1.91 kg/hour.